Impact of Water Vapor on the Development of a Supercell Over Eastern China - Wang, Hao; Hu, Zeyong; Liu, Peng; Zhang, Feimin (Frontiers in Earth Science, 2022)
In this study, the impact of water vapor on the improvement of precipitation simulation in a supercell event over eastern China is investigated by assimilating lightning data into the weather research and forecast (WRF) three-dimensional variational system. The results indicate that the vertical distribution of vapor plays a crucial role in convection precipitation simulation. The WRF alone fails to capture the vertical distribution of vapor, especially at higher altitudes, and vapor simulation is often weak in WRF. Assimilation of lightning data enhances the range and intensity of precipitation forecasts; assimilation of pseudo water vapor transformed from lightning data improves the convection intensification and updraft height of supercells by rectifying the vertical moisture profile. Lightning data assimilation can efficiently compensate for the paucity of observations during supercell growth, and the benefits of lightning data assimilation are concentrated in areas where lightning data is accessible. Further, the importance of microscale water vapor variations, which can be well represented by assimilating pseudo-water vapor, in representing the supercell's range and intensity is highlighted.